2016
DOI: 10.3109/10826084.2016.1152498
|View full text |Cite
|
Sign up to set email alerts
|

Pregaming and Emotion Regulation’s Relationship to Alcohol Problems in College Students: A Cross-Sectional Study

Abstract: Findings suggest that the relationship between pregaming and alcohol-related problems is complex. Accordingly, future studies should utilize event-level methodology to understand how emotion regulation strategies influence alcohol-related problems. Further, clinicians should tailor alcohol treatments to help students increase their use of cognitive reappraisal and decrease their use of suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…However, problems arising from both interpersonal difficulties and heavy drinking may be ameliorated by targeting improvements in cognitive reappraisal. Cognitive reappraisal is an integral component in both cognitive-behavioral therapy and motivational interviewing (e.g., Goldin et al, 2012; Morgenstern et al, 2012) It has been shown to be useful in decreasing engagement with alcohol in young adult populations (Brady, Tschann, Pasch, Flores, & Ozer, 2009; Norberg et al, 2016). There are many benefits to web-based, self-directed interventions for college drinking, particularly if they are adaptable to focus on specific skills such as cognitive reappraisal.…”
mentioning
confidence: 99%
“…However, problems arising from both interpersonal difficulties and heavy drinking may be ameliorated by targeting improvements in cognitive reappraisal. Cognitive reappraisal is an integral component in both cognitive-behavioral therapy and motivational interviewing (e.g., Goldin et al, 2012; Morgenstern et al, 2012) It has been shown to be useful in decreasing engagement with alcohol in young adult populations (Brady, Tschann, Pasch, Flores, & Ozer, 2009; Norberg et al, 2016). There are many benefits to web-based, self-directed interventions for college drinking, particularly if they are adaptable to focus on specific skills such as cognitive reappraisal.…”
mentioning
confidence: 99%
“…Thus, investigations of similar relations among diverse populations of young adult alcohol users is important to determine how pregaming confers risk to populations beyond college students. Finally, the present study rested on the assumption that pregaming was indicative of positive reinforcement based on past literature (e.g., Bachrach et al, 2012; Calhoun & Linden-Carmichael, 2022; Norberg et al, 2016), but future research is needed to test the extent to which acute subjective reward plays a role in relations among pregaming, drinking behavior, and impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ER more broadly, ER strategies have been examined in relation to psychopathology. This research has found, for instance, that habitual use of expressive suppression is positively related and habitual use of cognitive reappraisal is negatively related to depression (Gross & John, 2003), anxiety (McLean et al, 2007), eating disorders (McLean et al, 2007), and substance use (Norberg et al, 2016). Studies also reveal differential associations between ER strategies and specific psychopathologies.…”
Section: Introductionmentioning
confidence: 99%